Climate and COVID-19 in Latin America - Mora-Alvarado, Darner A. (2022)
Since ancient times, Hippocrates (460 BC) considered that the climate has influence on the origin and nature of diseases. In one of his writings called “Aphorisms” he claimed, “all diseases occur at all seasons of the year, but certain of them are more apt to occur and be exacerbated at certain seasons”. Based on the foregoing, the present study aims to determine the seasons of the year with the highest number of infections and deaths related to COVID-19 caused by the new coronavirus SARS-CoV-2 within 21 countries in Latin America. We analysed the evolution of the health crisis to identify the waves and the highest peaks of positive cases for each country during March 2020 -pandemic declaration by the World Health Organization- till June 18th, 2021. The results identified 53 waves: 13 (24,5%) during summer, 37 (69,8%) during winter, 3 (5.7%) during autumn and zero during spring. According to these findings, we recommend each country conduct more profound studies for stablishing possible correlations between solar radiation and number of infections by COVID-19.